BUILDING ENTREPRENURIAL INTENTION AMONG BUSINESS STUDENTS AT GREATER JAKARTA - Suresh Kumar; Devi Aprilia (Proceeding of the International Conference on Family Business and Entrepreneurship, 2021)
Purpose – The purpose of this paper is to explore the influence of entrepreneurship pedagogy roles towards change in attitude, change in perceived behavioral control, and change in the subjective norm in shaping entrepreneurial intention for the young generation to become entrepreneurs at their final year of study in Universities at Greater Jakarta.Design/methodology/approach – A survey instrument was distributed to some Greater Jakarta Universities students (Prasetya Mulia, Trisakti, Atma Jaya, Tarumanagara, and Pelita Harapan) and responses were collected in digital form. The analysis was performed on 204 responses using Structural Equation Modelling technique.Findings – The analysis revealed that the roles of entrepreneurship pedagogy towards change in attitude, change in perceived behavioral control, and change in subjective norm influence the intention of the final-year students to become an entrepreneur in Greater Jakarta.Keywords: Entrepreneurship Pedagogy, Entrepreneurial Attitudes, Perceived Behavioral Control, Subjective Norm, Entrepreneurial Intention.